HUBUNGAN TINDAKAN MANDIRI PERSONAL HYGIENE OLEH PERAWAT DENGAN TINGKAT KEPUASAN PASIEN IMOBILISASI DI RUANG RAWAT INAP RSUD DR. R GOETHENG TAROENADIBRATA PURBALINGGA - Indri Heri Susanti (Universitas Harapan Bangsa Purwokerto, 2014)
Patient immobilization has a very large dependence on the needs of nurses cared for themselves. Therefore, nurses in providing personal hygiene measuresshould be done as fully as possible in accordance with standard operatingprocedures issued by the hospital in order to satisfy the patient. Objective of studies to determine the relationship of independent action ofpersonal hygiene by nurses with a satisfaction levels of immobilization patient inthe inpatient room of RSUD dr. R Goetheng Taroenadibrata Purbalingga. The Type of study used correlational analysis studies with cross sectionalapproach. Samples of studied were the immobilization patient's in the inpatientroom of RSUD dr. R Goetheng Taroenadibrata Purbalingga as much as 69people. Data was collected used a questionnaire. Analysis data of research used chisquare test. The act independently of personal hygiene by the majority of nurses in theindependent category were 63 men (91,3%). The satisfaction levels ofImmobilization patient in the inpatient room the majority in the satisfied category as many as 64 people (92,8%). Statistical test results obtained by the x= 17.871 with p-value = 0.000 which is less than ï¡ = 0.05, it mean there was an independent act of personal hygiene by nurses with immobilization levels ofpatient satisfaction in inpatient hospitals room dr. R Goetheng Taroenadibrata Purbalingga of 2012 Key Words : personal hygiene, nursing, levels of satisfaction